Marketing Strategy & Competitive Positioning - Hooley, Graham J.; Piercy, Nigel F.; Nicoulaud, Brigitte (Harlow, England: Pearson Financial Times/Prentice Hall, 2012)
Pazarlama stratejisi
Keywords: Marketing -- Management; Pazarlama -- Yönetim